Engaging key stakeholders to overcome barriers to studying the quality of research ethics oversight. (January 2023) - Anderson, Emily E; Hurley, Elisa A; Serpico, Kimberley; Johnson, Ann; Rowe, Jessica; Singleton, Megan; Bierer, Barbara E; Cholka, Brooke; Chaudhari, Swapnali; Fernandez Lynch, Holly
The primary purpose of Institutional Review Boards (IRBs) is to protect the rights and welfare of human research participants. Evaluation and measurement of how IRBs satisfy this purpose and other important goals are open questions that demand empirical research. Research on IRBs, and the Human Research Protection Programs (HRPPs) of which they are often a part, is necessary to inform evidence-based practices, policies, and approaches to quality improvement in human research protections. However, to date, HRPP and IRB engagement in empirical research about their own activities and performance has been limited. To promote engagement of HRPPs and IRBs in self-reflective research on HRPP and IRB quality and effectiveness, barriers to their participation need to be addressed. These include: extensive workloads, limited information technology systems, and few universally accepted or consistently measured metrics for HRPP/IRB quality and effectiveness. Additionally, institutional leaders may have concerns about confidentiality. Professional norms around the value of participating in this type of research are lacking. Lastly, obtaining external funding for research on IRBs and HRPPs is challenging. As a group of HRPP professionals and researchers actively involved in a research consortium focused on IRB quality and effectiveness, we identify potential levers for supporting and encouraging HRPP and IRB engagement in research on quality and effectiveness. We maintain that this research should be informed by the core principles of patient- and community-engaged research, in which members and key stakeholders of the community to be studied are included as key informants and members of the research team. This ensures that relevant questions are asked and that data are interpreted to produce meaningful recommendations. As such, we offer several ways to increase the participation of HRPP professionals in research as participants, as data sharers, and as investigators.